Hedging Demands in Hedging Contingent Claims - Brandt, Michael W. (The Review of Economics and Statistics, 2003)
Minimum-variance hedging of a contingent claim in discrete time is suboptimal when the contingent claim is hedged for multiple periods and the objective is to maximize the expected utility of cumulative hedging errors. This is because the hedging errors are not independent. The difference between a minimum-variance hedge and the optimal multiperiod hedge is called the hedging demand and depends on the hedger's preferences, the characteristics of the contingent claim, the trading frequency and horizon, and most importantly the joint distribution of the contingent claim and the underlying security prices. Since modeling this joint distribution is empirically controversial, I examine nonparametrically the economic importance of hedging demands in the case of hedging Standard & Poor's 500 index options.